Premature Baby Care Training for Mothers: Efforts to Improve Skills in Caring for Premature Babies - Indarwati; Maryatun; Putri Azzahra, Hanifah; Octavia Ramadhani, Jessica (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
Caring for premature infants remains a major challenge for mothers, particularly in developing countries such as Indonesia. Infants born before 37 weeks of gestation require specialized care not only during hospitalization but also after discharge. Unfortunately, many mothers still lack adequate knowledge and skills to independently manage the care of premature infants, especially in key aspects such as safe bathing, maintaining body temperature to prevent hypothermia, providing optimal nutrition, and preventing infection. The limited availability of practical training and health education further constrains the transition from hospital-based to home-based care. This community service program was designed to strengthen maternal competence in caring for premature infants through structured training that combined theoretical instruction with hands-on practice. The activity was conducted at Soediran Mangun Sumarso Regional Hospital, Wonogiri, in May 2025, and involved six mothers with premature infants. The methods included health education, demonstrations, simulation exercises, and pre- and post-training evaluations. The results indicated a significant improvement in maternal competence across the four targeted skills. These findings highlight the effectiveness of practice-based educational interventions in preparing mothers for independent premature infant care. Furthermore, this initiative provides a foundation for developing scalable educational models that can reduce complications and improve the quality of life of premature infants, while empowering mothers as primary caregivers after NICU discharge.